Pengaruh Budaya Organisasi, Kompensasi, dan Disiplin Kerja Terhadap Kinerja Karyawan Di PT Samudera Trans Logistics - Amilia Duwi Nursinta; Iswati Iswati; Eny Sulistyowati (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to examine the influence of organizational culture, compensation and work discipline on employee performance at PT Samudera Trans Logistics. The background of this research is that we can get a good workforce by improving good organizational culture, appropriate compensation and continuously increasing work discipline. PT Samudera Trans Logistics, a logistics company, is facing complaints that the level of employee discipline in entering the office on time is still low. This is also reinforced by company data which shows employee absenteeism data for January - March 2024. Therefore, it is important to carry out this research so that it can help companies improve organizational culture and discipline. The purpose of this research is to determine: the influence of organizational culture on employee performance, the influence of compensation on employee performance, and the influence of work discipline on employee performance. The population of this research is all employees at PT Samudera Trans Logistics, totaling 40 people. Data collection was carried out using a questionnaire which was measured using a Likert scale. Data analysis techniques used include descriptive tests, validity tests, reliability tests, normality tests, multicollinearity tests, multiple linear regression tests, coefficient of determination tests, t tests, and F tests. Simultaneously, the variables Organizational Culture, Compensation, and Career Discipline have an effect on Employee Performance variable. The coefficient of determination (R square) shows that the variables Organizational Culture, Compensation and Work Discipline have an influence of 63,4% on the Employee Performance variable while the remaining 36,6% is influenced by other variables.